Comprehensive Analysis of Therapy-Related Messenger RNAs and Long Noncoding RNAs as Novel Biomarkers for Advanced Colorectal Cancer - Li, Jibin; Ma, Siping; Lin, Tao; Li, Yanxi; Yang, Shihua; Zhang, Wanchuan; Zhang, Rui; Wang, Yongpeng (Frontiers in Genetics, 2019)
Colorectal cancer (CRC) is one of the most common types of human cancers. However, the mechanisms underlying CRC progression remained elusive. This study identified differently expressed mRNAs, lncRNAs and snoRNAs between pre-therapeutic biopsies and post-therapeutic resections of locally advanced colorectal cancer by analyzing a public dataset, GSE94104. We identified 427 dysregulated mRNAs, 4 dysregulated lncRNAs and 19 dysregulated snoRNAs between pre- and post-therapeutic locally advanced colorectal cancer samples. By constructing PPI network and co-expressing networks, we identified 10 key mRNAs, 4 key lncRNAs and 7 key snoRNAs. Bioinformatics analysis showed therapy related mRNAs were associated with nucleosome assembly, chromatin silencing at rDNA, negative regulation of gene expression, DNA replication. therapy related lncRNAs were associated with cell adhesion, extracellular matrix organization, angiogenesis, sister chromatid cohesion. And therapy related snoRNAs were associated with DNA replication, nucleosome assembly, telomere organization. We thought this study provided useful information for identifying novel biomarkers for CRC.